Konseling Pastoral terhadap Jemaat yang Mengalami Perasaan Tidak Berharga (Pusat Riset dan Inovasi Nasional, 2024)
This article addresses the pastoral problem of congregants who experience persistent feelings of worthlessness, a condition that often appears at the intersection of shame, fragile self-worth, social isolation, and distorted religious interpretation. The objective is to construct a Christian pastoral counseling framework that is biblically grounded, psychologically informed, and ecclesially accountable. This study uses a qualitative constructive literature design through critical synthesis of recent journal articles and classical pastoral counseling. The analysis identifies four main findings. First, worthlessness should not be reduced to moral weakness or lack of faith because it involves psychological, relational, and spiritual dynamics. Second, churches may either intensify shame through stigma and spiritual reductionism or become restorative communities through hospitality, lament, and safe accompaniment. Third, pastoral counseling requires a movement from empathic assessment, validation, and narrative clarification toward theological reframing of identity in Christ. Fourth, responsible pastoral care includes collaboration with mental health professionals when risk, trauma, or clinical symptoms exceed pastoral competence. The implication is a constructive model in which pastoral counseling helps congregants reinterpret self-worth through grace, embodied community, and disciplined referral rather than through advice-giving or doctrinal correction alone.